Basic and clinical studies on NM441 in urological field - Ohmori, Hiroyuki; Tsugawa, Masaya; Sakuramoto, Koushi; Ono, Noriaki; Kumon, Hiromi; Monden, Kouichi; Hata, Kazuhiro; Hayata, Shunji; Nanba, Katsuichi; Suyama, Bunzo; Watanabe, Toyohiko; Nasu, Yoshitsugu; et al. (Japanese Journal of Chemotherapy, 1996)
We studied the antibacterial activity and clinical efficacy of NM441, a new oral quinolone, which is the prodrug of the biologically active NM394. 1) Antibacterial activity: We measured the MICs of NM394 against 200 clinical isolates from urinary tract infections (UTI), and compared them with those of ofloxacin (OFLX), ciprofloxacin (CPFX), norfloxacin (NFLX), sparfloxacin (SPFX), lomefloxacin (LFLX) and tosufloxacin (TFLX). The antibacterial activities of NM394 against gram-positive bacteria were a little inferior to those of SPFX, LFLX or TFLX, but were comparable to those of OFLX or CPFX. On the other hand, against gramnegative bacteria, in general, antibacterial activities of NM394 were superior to those of other new quinolones. 2) Clinical efficacy: According to the criteria of the Japanese UTI Committee, the overall clinical efficacy rate was 100%(9/9) for uncomplicated UTI and was 88.9%(24/27) for chronic complicated UTI. Bacteriologically, 25 of 29 strains (86.2%) were eradicated for chronic complicated UTI. 3) Side effect: Nausea was observed in 1 patient (2.2%), and an abnormal laboratory finding was observed in 1 patient (2.2%), that showed transient eosinophilia.